Implementation of APPGM-SDG Solutions Initiatives and Impact Evaluations in Sarawak's South Region - Isnin, Nadrawina; Junaidi, Noni Harianti; Omar, Arenawati Sehat; Mahmud, Noorfadhleen; Ujang, Rudy (Journal of Technical Education and Training, 2025)
As public awareness of the Sustainable Development Goals 2030  has grown, the Malaysian Parliament formed the All-Party Parliamentary Group Malaysia on the Sustainable Development Goals (APPGM-SDG). As part of a bipartisan effort to enhance the implementation of SDG targets in Malaysian parliamentary seats, one of the goals of this research is to investigate the SDG implications of beneficiary solution initiatives. A team is tasked with assembling a report that combines the impact evaluation of SDG initiatives in the Sarawak South Region. Through document analysis, focus groups, and site visits, the regional research team investigated, from December 2023 to February 2024, how the knowledge, skills, networks, and systems of these projects as well as psychology affect the beneficiaries of the solution projects. The paper also addresses the efficiency with which solution providers manage and execute projects, the impact on the beneficiaries, the alignment and mapping of the solution providers' and impact evaluation with the SDG goals and APPGM-SDG modules, and the identification of obstacles and recommended solutions. The study also includes the qualitative and quantitative analysis that the assessors conducted using standardised questionnaires to measure the following six (6) crucial factors: Deep, Clear, Wide, High, SDG and Gender. The primary conclusion is that the goal of all solution initiatives is to eradicate poverty. It is intended that this paper's discussion of the difficulties would better assist project implementers’ and policymakers in making decisions, designing programmes, and writing policy papers, especially when it comes to the economic, social, and environmental domains with specific SDG deliverables and target audiences in mind.  With the aim to improve communication between stakeholders and provide more substantial prospects for society after project execution, the research suggests more visitations approaches.